Tobacco in the news: an analysis of newspaper coverage of tobacco issues in Australia, 2001. (23rd July 2003) - Durrant, R; Wakefield, M; McLeod, K; Clegg-Smith, K; Chapman, S
Abstract : Objective: To assess the extent and nature of newspaper coverage of tobacco related issues in Australia in 2001. Design: Content analysis of newspaper articles. Subjects: All articles (n=1188) at least seven lines long and containing at least one paragraph focused on tobacco in all major Australian national and State capital city newspapers (n=12) in 2001. Main outcome measures: Number of articles, month of publication, State in which newspaper published, prominence of article, type of article, article theme, and slant of article relative to tobacco control objectives. Results: The number of tobacco articles varied considerably in different months over the course of the year, from a low of 51 in December to a peak of 180 in May. The most frequent theme was secondhand smoke issues (30% of articles), with the second most dominant theme related to education, prevention, and cessation programmes and services (20%). Events that were covered were predominantly positive for tobacco control: 62% of articles were related to events that were positive, compared with 21% that were negative for tobacco control objectives. Excluding news articles, the opinions expressed by the authors of articles were also mainly positive (61%) rather than negative (22%) for tobacco control objectives. The amount of coverage of and population exposure to tobacco focused articles showed considerable variation across different Australian States, with Victoria having the highest frequency and rate of articles and the most media impressions per capita throughout 2001. Conclusions : Coverage of events and opinions related to tobacco in Australian newspapers in 2001 was generally positive for tobacco control objectives. Given that over 2 million individuals (out of a population of 19 million) were potentially exposed to tobacco related newspaper articles per day in Australia, this represents good news for tobacco control advocates. The variation in news coverage in different States and at different times in the year, however, illustrates how a combination of local events and advocacy efforts may at times combine to make tobacco more newsworthy. Understanding which tobacco issues are most likely to be covered and the nature of the coverage about them provides valuable feedback for tobacco control advocates and is a useful gauge of actual events as well as the tobacco related agendas promoted by the press.